PERKIRAAN POTENSI DAN UTILISASI ENERGI PANAS BUMI UNTUK PEMANFAATAN LANGSUNG DI PROSPEK LELES, CIANJUR, JAWA BARAT: THE POTENTIAL AND UTILIZATION OF GEOTHERMAL ENERGY ASSESSMENT FOR DIRECT UTILIZATION IN THE LELES PROSPECT, CIANJUR, WEST JAWA - Nugraha, Husin; Rina Wahyuningsih; Dede Iim; Dadan Wildan (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
This research activity aims to estimate the potential and utilization of geothermal energy for direct use in Prospect Leles, Cianjur Regency, by applying technical instructions on calculating the potential and utilization of geothermal energy for direct use. The Leles prospect has eight heat sources for direct utilization of geothermal energy: five hot springs, one hot water drilled well, and two hot water bathing pools. Two pools are categorized as utilized, with the installed capacity of one hot spring with proven reserves. Meanwhile, the remaining five hot springs are still categorized as measurable resources. The total installed capacity of the two hot spring pools is 38.85 kWt with an annual utilization of 1.23 TJoules per year or 0.34 GWh per year with an estimated capacity factor of 33.3%. With this capacity, the ratio of installed capacity to proven reserves is still very small, only 1.41%. Meanwhile, the total potential of the Leles Prospect is 3.3 MWt with details of proven reserves of 2,592 kWt and measured resources of 704 kWt. The recommendation for direct use is to increase the utilization installation, either in parallel, a pool can be made for swimming, bathing, and a jacuzzi, and in cascading with aquaculture, such as shrimp or catfish.